Pelatihan Literasi Keuangan Tentang Pentingnya Management Investasi Bagi Gen Z - Iman Supriadi; Rahma Ulfa Maghfiroh; Kusuma Adi Rahardjo; Tri Wahjoedi; Rukhul Abadi; Dewi Mumpuni Yudowati; Nuruddin (AMMA : Jurnal Pengabdian Masyarakat, 2024)
This paper discusses community service efforts through financial literacy training focused on the importance of investment management for generation Z. This paper aims to improve gen Z's understanding of financial investment, stimulate their interest in investing, and provide effective investment management skills. The training method involves delivering theoretical information, case studies, and investment simulations. Results from the study showed significant improvements in financial literacy understanding and investment management skills among participants. The program also successfully stimulated gen Z's interest in investing wisely. Thus, financial literacy training can be an effective instrument to help generation Z manage their finances smartly and understand the positive impact of investment management in achieving long-term financial goals.